Penapisan Fitokimia dan Aktivitas Antioksidan pada Ekstrak Kulit Batang Cyathocalyx sumatranus Scheff - Masykur Masykur; Nurdin Nurdin; Lukmanul Hakim; Rosnizar Rosnizar; Widya Sari; Bella Sabilla Novita; Rabiatul Adawiyah; Siti Sari Azyati; Yuni Arifa; Ria Ceriana (Journal of Pharmaceutical and Health Research, 2026)
This study aims to determine the phytochemical composition and antioxidant activity of an ethanol extract of the bark of Cyathocalyx sumatranus Scheff., which shows potential as a natural hepatoprotective agent. Oxidative stress plays a central role in the pathogenesis of liver damage, and antioxidant activity is widely recognised as one of the key indicators supporting the hepatoprotective potential of medicinal plants. The research methodology employed was a laboratory-based experimental study involving phytochemical screening, thin-layer chromatography (TLC) analysis, and testing of antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Bark samples were extracted using 96% ethanol via maceration for 3 × 24 hours. The results of the phytochemical screening indicated that the ethanol extract of the bark contained secondary metabolites in the form of alkaloids, terpenoids, flavonoids, phenolics and tannins. TLC analysis revealed the presence of alkaloids and steroids in the extract. Antioxidant testing was carried out using various concentrations of the extract, namely 50 μg/mL, 75 μg/mL, 100 μg/mL, 125 μg/mL and 150 μg/mL, with vitamin C as a control. The antioxidant activity tests showed that an increase in extract concentration was directly proportional to an increase in the percentage of DPPH free radical inhibition. The highest inhibition value was obtained at a concentration of 150 μg/mL, amounting to 62.454%. The results of the linear regression analysis indicated an IC₅₀ value of 94.906 μg/mL, which falls within